The role of market competition for knowledge competencies,R&Dand innovation : an empirical analysis for German firms - Basit, Shoaib Abdul (2022)
Purpose – Knowledge competencies and (R&D) activities are one of the most important sources of innovation and have been widely discussed in the literature. In comparison, the role of the competitive environment for the innovation activities of firms is still open to debate and has not been fully understood yet. Therefore, this paper intends to provide new evidence on the interaction between knowledge competencies and R&D activities of firms on the one side and their competitiveness in the market environment on the other. In particular, the moderating function of market competition is explored. In this respect, the analysis covers the main innovation types as well as both sectors, manufacturing and services. Design/methodology/approach – The empirical analysis is based on a three years panel dataset of German manufacturing and service firms obtained from Mannheim Innovation Panel (MIP) and Community Innovation Surveys (CISs: 2011, 2013 and 2015). For the estimation, a binary instrumental variable treatment model with Heckman selection method is used. Also, it provides a suitable approach to estimating the binary variables in order to cope with endogeneity concerns. Findings – The estimation results show thatR&D activities and knowledge competencies are positively related to innovation activities of different types conditioned on firms’ specific perception of their competitive environment, in terms of outdated products/services as well as strong competition from abroad. Most importantly, the results from the moderation estimation reveal that there is a significant difference between the manufacturing and service sector. Service firms engage more in internal R&D activities on generating product innovations while the manufacturing firms conduct more external R&D on specific types of innovation. Further, the authors find that strong competition from abroad positively and significantly reinforces the effect of knowledge competencies on innovation activities for more types in services than in manufacturing. In contrast, outdated products and services tend to decline the effect of knowledge competencies for some innovation types in both sectors.The authors also observe a positive and significant reinforcement effect on knowledge competencies. However, it is found more beneficial for service firms since they can employ more innovation strategies. Originality/value – The focus of the study is mainly on the impact of firms’ competitive environment on innovation activities in various types through its interaction with knowledge competencies andR&D activities, across manufacturing and service firms.